Providing Hearing Education and Resources for Underserved Populations (HEAR-UP) in our Local Neighborhoods - Coyan, Kathleen Costigan; Mormer, Elaine (Seminars in Hearing, 2020)
Healthcare services in the United States are difficult to access for at least 10% of our population. Moreover, hearing healthcare services, including hearing aids, are largely inaccessible even for those individuals who may have health insurance and access to healthcare. Humanitarian audiology has been recognized as a means of supplying hearing services and devices to underserved populations around the globe. However, little has been publicized about humanitarian audiology projects taking place in local communities within the United States. This article describes one such project that has been in place in Pittsburgh, PA, for the past 4 years. This service results from collaboration across a collection of healthcare, community service, charitable, and educational organizations. The resources necessary to create similarly sourced services in other U.S. locations are described. Challenges and solutions for this local form of humanitarian audiology are discussed.
Keywords: underserved; Federally Qualified Health Clinic (FQHC); free clinic; hearing health access